Experimental verification of the efficiency of the methodology of differentiated formation of english lexical competence in reading of future linguists - Kravchenko, Andrii (ScienceRise: Pedagogical Education, 2019)
The article presents the results of the experimental verification of the effectiveness of the methodology of differentiated formation of English lexical competence in reading of future linguists, the planning, preparation and conduct of the experiment are described as well as the criteria and norms for evaluating lexical knowledge and receptive skills in reading; experimental verification of the effectiveness of author’s methodology and developed methodological recommendations are also proved. The author’s methodology is implemented in the model of the organization of the learning process, which covers the differentiation of learning objectives and expected results, teaching objects and subjects of training; learning elements; content, methods, forms of organization and control of students’ educational activities. The micro-module is set as the minimum unit of the education organization. It comprises 6 hours of in-class work and 6 hours of independent work. It is thematic and covers about 100 new words, according to which the sentences, the phrasal unity, the texts are chosen, and the subsystem of exercises and tasks is organized. The model is synchronized: students perform the same type of work at the same time, but the content of the exercises and the nature of the tasks varies. It is found out that the effectiveness of the formation of English lexical competence in reading of future linguists is high, provided that differentiated groups are created according to the criterion of learning (low / sufficient / high); the objectives and expected learning outcomes for each differentiated group is given; provided that the content and nature of the exercises and tasks, the control over their implementation are monitored, and the adherence to the phases of the learning process is controlled. To assess students, the following criteria were taken: the correctness of understanding of the lexical unit, its denotative and connotative meaning in the speech; correctness of content communication establishing; degree of understanding of the implications and concepts in the text; extralinguistic information related to the lexical unit; degree of understanding of the content and meaning of the text; correctness and depth of search / analysis when solving lexicological tasks. We were able to trace the positive dynamics of the experimental group as a whole and each differentiated subgroup (depending on the initial level of learning) in particular. The reliability of the results of the experiment were proved by the Mann-Whitney method